The status of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) in Greece: A case of an exotic predator that failed to establish? - Kontodimas, D. C.; Stathas, G. J.; Martinou, A. F. (ENTOMOLOGIA HELLENICA, 2008)
During 1994 -1999 several hundred thousands of Harmonia axyridis adults were released at various cultivations infested by aphids (citrus, vegetable and bean crops, maize, etc.) or in urban places on ornamental plants in central and southern Greece (mainly Attica and Peloponnessos region) as well as on several islands. During 1995-2007, samplings were conducted in some areas, in spring just before any new releases, in order to determine if H. axyridis overwintered in the field. In spring 1995 (the year that followed the first releases) as well in spring 1996-97 and 2000-07, no presence of H. axyridis was recorded in any of the orchards where the predator had been released. Only in spring 1998 and 1999 small colonies (<50 individuals) of overwintered H. axyridis adults were observed in Attica region. The above results indicate an inability of the H. axyridis released populations to establish in Greece, although in some areas this species became an important biocontrol agent during the season. In addition, some data collected regarding the composition of native coccinelid species pre- and post- release of H. axyridis could be an indication of no adverse effects imposed by H. axyridis on the native coccinellid fauna in Greece. Despite that, any re-initiation of releases of H. axyridis would not be wise because of its multiple negative effects observed in other countries of Europe and the USA. Contrary to this, the application of a survey and monitoring programme that will allow us to be prepared in case of a possible invasion of H. axyridis from northern Europe is suggested.